2009
DOI: 10.1002/qaj.433
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance within the scope of Good Clinical Practice (GCP)—what is the cost of GCP‐related activities? A survey within the Swedish Association of the Pharmaceutical Industry (LIF)'s members

Abstract: SummaryThe bureaucracy that the Good Clinical Practice (GCP) system generates, due to industry over-interpretation of documentation requirements, clinical monitoring, data verifications etc. is substantial. The aim of this study was to estimate the percentage cost of all such GCP-related activities within phase III clinical trials performed in Sweden in 2005. Method: An electronic questionnaire on ICH GCP-activities and their related costs was sent to 47 of the 60 member companies of the Swedish Association of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…Carraro and Plebani 18 Found error rates of 3.2% and 7.2% in imprecise data entry of specific data points. Funning et al 5 Reported a widespread misunderstanding that the quality of a clinical trial is dependent on the degree of errors discovered. Grahnen et al 19 Illustrated that transcription errors of up to 5% in source data had no significant impact on the outcome of a trial.…”
Section: Us Department Of Health and Humanmentioning
confidence: 99%
See 1 more Smart Citation
“…Carraro and Plebani 18 Found error rates of 3.2% and 7.2% in imprecise data entry of specific data points. Funning et al 5 Reported a widespread misunderstanding that the quality of a clinical trial is dependent on the degree of errors discovered. Grahnen et al 19 Illustrated that transcription errors of up to 5% in source data had no significant impact on the outcome of a trial.…”
Section: Us Department Of Health and Humanmentioning
confidence: 99%
“…SDR is a quality management method to evaluate critical processes, including those not associated with a data field in the CRF. On-site monitoring with a primary purpose of SDV is resource intensive, accounting for up to 25% of the total clinical trial cost, 5 and SDV predominantly detects random errors that likely have little impact on the results of clinical trials. Despite this evidence and encouragement from regulators to develop strategic monitoring processes, SDV remains widely engrained in the clinical trial industry as the primary focus of on-site monitoring visits.…”
Section: Introductionmentioning
confidence: 99%
“…SDV is costly and reported to account for an average of 25% of the entire clinical trial budget . The cost‐benefit evaluation of SDV has historically been difficult as very few data are available on the actual benefits of applying a 100% SDV approach.…”
Section: Introductionmentioning
confidence: 99%
“…Results from a survey of Swedish pharmaceutical companies in 2005 suggested that fifty percent of the cost of GCP-related activities in phase III trials was due to SDV, with an estimated actual cost of SDV for a phase III program estimated as 90 million US Dollars [7]. In a different study, on-site monitoring was estimated to represent approximately 25 to 30% of costs in phase III cardiovascular clinical trials [8].…”
Section: Introductionmentioning
confidence: 99%